Reproductive performance of Tswana ewes and Boer does in south-eastern Botswana - Seabo, D.; Aganga, A.A.; Mosienyane, M. (International Livestock Research Institute, 1996)
The reproductive performance over a five-year period (198993) of Tswana ewes and Boer does kept under semi-intensive management at Estate Management Unit farm of the College at Sebele-Gaborone, Botswana, was analysed. A total of 70 lambings and 152 kiddings involving 202 lambs and 288 kids were subjected to statistical analysis. The parameters studied were age at first parturition (AFP), parturition intervals (PI), annual parturition rate (APR), birth weight (BOO) and correlation between dam weight (DW) and young birth weight. The results showed that for Tswana ewes, AFP, PI, APR and BW were 18.00±1.39 months, 365±28.50 days, 1.00 and 3.30±0.89 kg, respectively, while for Boer goats they were 18.00±0.69 months, 350±2.4 days, 1.00 and 3.23±0.76 kg, respectively. Tswana ewes are seasonal breeders, they lamb in late spring and early summer (October-December). Male to female sex ratio was 49.0% for the 202 lambs and 52.78% for the 288 kids recorded. The rate of single and twin lambings were 80.59% and 19.41%, respectively, while the rate of single, twin, triplet and quadruplet kiddings were 28.29%, 53.28%, 16.45% and 1.32%, respectively. Mortality and stillbirths were 3.43% and 0.5%, respectively, for sheep while mortality, stillbirths and abortions for goats were 10.42%, 2.78% and 0.66%, respectively. The analyses show that Tswana ewes and Boer does are early maturing breeders. There was a poor correlation (r2 = 0.02 for sheep r2 = 0.04 for goats) between the dam's body weight and the young's birth weight.